ANALYSIS OF THE EFFECTIVENESS OF GOLD AND SUKUK AS A HEDGE - Windi Wahyuni Simanjuntak; Darwis Harahap; Abdul Nasser Hasibuan (RADJA PUBLIKA, 2024)
This study aims to analyze and compare the effectiveness of gold and sukuk as hedging instruments. Using historical data for the period 2014-2023, the study was conducted using a quantitative methodology through granger causality test analysis, One way ANOVA, Paired sample t-test. The results of the study show that gold has a higher effectiveness as a hedging instrument, as evidenced by a correlation of 0.72 (compared to sukuk 0.31), beta 1.25 (compared to sukuk 0.45), and Sharpe Ratio 1.85 (compared to sukuk 1.12). In periods of high inflation such as 2014 (8.36%) and 2022 (5.95%), gold showed a faster and more proportional response than sukuk. This study concludes that gold is a more effective hedging instrument than sukuk in the context of the Islamic financial market.